Kesantunan Berbahasa di Pelabuhan Talango Kab. Sumenep: Sebuah Tinjauan Sosiolinguistik - Tri Sutrisno (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2023)
The issue of language politeness is an interesting thing, especially when it occurs in a place like a port which is synonymous with a meeting place for individuals of all kinds, both from socio-cultural as well as language or ethnicity. The formulation of the problem in this research is how to use politeness in Talango Harbor? This research is qualitative descriptive research because it reveals the quality of language politeness objectively in a group of people at Talango Harbor in the form of dialogue recorded by the researcher. Based on the results of the study, the conclusions of this study are as follows. (1) At the lexical level, there are still many deviations in the use of politeness in Talango Port, mainly by boatmen to traders and passengers who are routine and very familiar. (2) At the phrase level there are still deviations, especially those committed by boatmen to traders and passengers who are routine and very familiar. (3) At the sentence level there are still deviations. This happens because of the original nature that really likes to use language that is not polite to those who are routine and familiar. However, it was found that for those who were not familiar and had a slightly higher social status at the lexical level, phrases and sentences were quite polite.